Comparison of three methods for isolation of nucleic acids from membranate inner ear tissue of rats - KONG, Wei-jia; WANG, Ying; WANG, Qiong; HAN, Yue-chen; HU, Yu-juan (Chinese medical journal, 2006)
Background Mitochondrial DNA mutations have been found in sensorineural deafness. The aim of this study was to compare three methods for extraction of nucleic acid from membranate inner ear tissue of rats. Methods Alkaline denaturation, a conventional phenol-chloroform method and Trizol reagent were respectively used to extract the slight nucleic acid from membranate inner ear tissue of rats. We assessed the amount and quality of nucleic acid using a UV-spectrometer and polymerase chain reaction （PCR）. Results The yield and purity （OD260/OD280） of DNA from inner ear tissue using the phenol-chloroform method was the highest of the three methods. Mitochondrial DNA （mtDNA） fragment can be amplified by PCR from nucleic acid prepared by all methods, while no nuclear DNA （nDNA） fragment can be amplified by method of alkaline denaturation. Both nuclear and mitochondrial genes could be amplified by reverse transcriptional PCR from the RNA prepared by Trizol reagent. Conclusion Adequate amount and high-quality of mtDNA, nDNA and RNA were obtained from unilateral membranate inner ear tissue of rats. Method of alkaline denaturation could be chosen when mtDNA without nDNA was needed, while phenol-chloroform method was suitable for extracting total DNA （including nDNA and mtDNA）： method with Trizol reauent was suitable for extractinu total RNA and total DNA.